Digital-visual Stakeholder Ethnography. (December 2017) - Pink, Sarah; Postill, John; Leder Mackley, Kerstin; Astari, Nadia
In this article, we discuss how new configurations of stakeholders are implicated and can be conceptualised in digital-visual applied and public ethnography. We set the discussion in the context of the increasing calls for researchers to have impact in the world and the ways that digital technologies are increasingly implicated in this. In doing so, we situate ethnographic practice and stakeholder relationships within a digital-material world. To develop our argument, we discuss examples of two recent digital video ethnography projects, developed in dialogue with anthropological theory, with online digital-visual applied and public dissemination outputs. As we show, such projects do not necessarily have one direct applied line, but rather can have multiple impacts across different groups of stakeholders.